Significance of plasma NT-proBNP levels as a biomarker in the assessment of cardiac involvement and pulmonary hypertension in patients with sarcoidosis - Handa, T.; Nagai, S.; Ueda, et al., S. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Background: Cardiac involvement and pulmonary hypertension (PH) are life-threatening complications in sarcoidosis. Objective: This study aimed to investigate the utility of plasma NT-proBNP in the assessment of these conditions in sarcoidosis patients. Study Design and Methods: A prospective, observational study was performed on 150 consecutive Japanese sarcoidosis patients. Doppler echocardiography was performed in all subjects, and those who were successfully evaluated for PH status were included in the analysis. Cardiac sarcoidosis was diagnosed based on Japanese guidelines, and PH was defined as estimated systolic pulmonary artery pressure (sPAP) ≥ 35 mmHg. The diagnostic accuracy of NT-proBNP according to the presence of cardiac sarcoidosis and PH was assessed based on receiver-operator characteristic (ROC) curves. Results: 130 subjects were successfully evaluated for PH status. Of these, 29 met the diagnostic criteria of cardiac sarcoidosis, and 21 were diagnosed with PH. Plasma NT-proBNP levels were significantly higher in patients with cardiac sarcoidosis (p<0.0001). Stepwise regression analysis showed that presence of cardiac sarcoidosis, decreased ejection fraction and increased sPAP were all independently associated with higher plasma NT-proBNP levels. Plasma NT-proBNP showed good accuracy in identifying patients with cardiac sarcoidosis (area under the ROC curve; AURC = 0.913).However, even when patients with cardiac sarcoidosis were excluded, plasma NTproBNP levels could not be used reliably to identify patients with PH (AURC = 0.681). Conclusion: In patients with sarcoidosis, plasma NT-proBNP levels are a useful biomarker to identify cardiac involvement, but not to identify PH.